Optimum collection and concentration strategies of hydrobionts excess biomass in biological surface water purifying technologies - Malovanyy, Myroslav; Tymchuk, Ivan; Balandiukh, Iurii; Soloviy, Christina; Zhuk, Volodymyr; Kopiy, Maria; Stokaliuk, Oleh; Petrushka, Kateryna (Видавництво Львівської політехніки, 2021)
The analysis of perspective collection and concentration technologies of excess biomass in the technologies of wastewater and surface water biological treatment with the use of aquatic organisms has been carried out. The scheme of a life cycle of the aquatic organisms in wastewater and surface water treatment technologies has been proposed. The analysis of technological approaches for biomass collection of three types: aquatic plants and macroalgae; aquatic plants with a developed root system and microalgae of aquatic organisms has been carried out. A strategy for concentrating microalgae has been proposed. The high efficiency of the coagulation-flocculation gravitational thickening method of freshwater microalgae suspensions of the Microcystis aeruginosa species has been confirmed in laboratory conditions.
Keywords: hydrobionts; excess biomass; collection; concentration; surface and wastewater; aquatic plants; microalgae